Food and feeding habits of Grey mullet, Rhinomugil corsula (Hamilton, 1822) in the Sitakunda coast of Bay of Bengal, Chattogram, Bangladesh - Ara, Syeda Ismat; Azadi , M A; Nasiruddin, Munira (Bangladesh Journal of Zoology, 2024)
A total of 240 Grey Mullet (Rhinomugil corsula), collected from the Sitakunda coast of the Bay of Bengal, were used for the analysis of food and feeding habit during the period from January 2017 to December 2017. Thirteen major types of food items, viz., blue-green algae, green algae, diatoms, desmids, dinoflagellates, rotifer, copepod, cladoceran, other crustacean, benthic organisms, semi-decomposed plant parts, decayed organic matters and sand and detritus were found in the gut of the fish. The rank of food preference – according to index of preponderance (IP) – was Diatoms (71.88%) > Green algae (10.01%) > Copepods (9.94%) Blue-green algae (4.42%) > Sand and detritus (2.32%) > Decayed organic matter (2.17%) > Rotifers (1.13%) > Semi-digested plant parts (1.02%) > Desmids (0.71%) >Cladocerans (0.45%) > Crustacea (0.26%) > Benthic organism (0.18%) > Dinoflagellates (0.11%). The highly fed fishes (gorged stomach) were found in May (100%), October (85%), June (65%), August (65%), September (50%), November (50%) and March (43%); whereas the highest empty guts were found in January (45%). Length wise feeding intensity revealed that smaller fishes (9-15 cm) were more active feeder than those of the larger fishes of 15 cm above. It can be inferred that Rhinomugil corsula primarily functions as an iliophagus bottom feeder, mainly consuming planktonic organisms, particularly diatoms. Bangladesh J. Zool. 52(1): 81-94, 2024